2020
DOI: 10.3389/fpsyg.2020.02064
|View full text |Cite
|
Sign up to set email alerts
|

How to Promote Ethnic Village Residents’ Behavior Participating in Tourism Poverty Alleviation: A Tourism Empowerment Perspective

Abstract: Local villagers are regarded as the main part of tourism development in the ethnic village, their participation in tourism poverty alleviation has a vital impact on sustainable tourism development and poverty reduction. Based on the planned behavior theory and capacity approach theory, we investigated the influence of tourism empowerment on ethnic village residents' behavior participating in tourism poverty alleviation, especially focusing on the mediating effect of participation willingness and the moderating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Also, few negative influences can be observed. The most controversial is the number of tourists (Yang et al, 2020). As the prosperity of the world increases, more people are able to enjoy trips that were once only possible for the select few.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, few negative influences can be observed. The most controversial is the number of tourists (Yang et al, 2020). As the prosperity of the world increases, more people are able to enjoy trips that were once only possible for the select few.…”
Section: Resultsmentioning
confidence: 99%
“…This inevitably leads to disappointment as people are reduced to a melancholy mass (Pompurová et al, 2020). The positive relationships between tourism psychological empowerment, tourism economic empowerment, and participation willingness would be more robust when village residents' participation ability is higher (Yang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Farmers can acquire additional income as their individual abilities are reinforced. Therefore, as Yang et al (2020b) and Wang and Xiang (2017) stated, motivation, opportunity, and ability have positive impacts on farmers' participation in tourism. However, in comparison, the motivation of farmers has the greatest impact on participation, whereas the opportunity to participate has the least impact.…”
Section: Discussionmentioning
confidence: 99%
“…In tourism activities, tourists' motivation and opportunity are positively related to their participation, but not significantly related to their ability (Leung and Bai, 2013). Therefore, is the tourism participation of farmers in border tourism areas affected by the three components (Wang and Xiang, 2017;Yang et al, 2020b)? Based on this question, this study proposes the following: Hypothesis 1a (H1a): Participation motivation has a significant positive impact on involvement level.…”
Section: Moa Theory and Participationmentioning
confidence: 99%
“… Mihalič (2000) reported that tourist destinations, tourist routes, and the tourism industry are the main factors to use when measuring tourism competitiveness. Scholars have found that the main influencing factors of tourism competitiveness are human resources, talent competition, image marketing, and knowledge-based management ( Wei, 2000 ; Nie, 2006 ; Zhang et al, 2011 ; Cvelbar et al, 2016 ; Yang et al, 2020 ; Lan et al, 2021 ). In addition, tourists’ perceptions and the level of scientific and technological development of tourist destinations have a significant impact on the competitiveness of urban tourism destinations.…”
Section: Literature Reviewmentioning
confidence: 99%